Students’ Difficulties In Speaking English Of The Eighth Grade Students Of SMP Negeri 35 Samarinda - Della Seventina; Aridah Aridah; Didik Sucahyo (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2021)
The current study aimed to analyze the levels of students’ English speaking difficulties and to investigate the most frequent factor causing why students perceived the English speaking difficulties. It employed descriptive quantitative, in which the data obtained from 75 junior high school students of SMP Negeri 35 Samarinda, who responded a-five point Likert scale questionnaire through asynchronous online Google Form. The computer program of SPSS.22 was utilized in the data analysis. It showed that the level of English speaking difficulties perceived by the students was high categorized that proved with the mean score 3.28. Then, the most factor that caused on the English speaking difficulties faced by students was academic and conversational English skills (Mean=3.48), followed by linguistics obstacles (M=3.30), speech processing difficulties (M=3.29), negative effects (M=3.25), and finally access to speaking opportunities (M=2.99).